The geopolitics of spectacle: space, synecdoche, and the new vapitals of Asia - Koch, Natalie (Cornell University Press, 2018)
Why do autocrats build spectacular new capital cities? In The Geopolitics of Spectacle, Natalie Koch considers how autocratic rulers use "spectacular" projects to shape state-society relations, but rather than focus on the standard approach--on the